Tax burden and migration: A political economy theory and European evidence - Assaf Razin; Efraim Sadka; Phillip Swagel (Institute for Advanced Studies (IHS), 1998)
The extent of taxation and redistribution Policy is generally determined as a political-economy equilibrium by a balance between those who gain from higher taxes/transfers and those who lose. In a stylized model of migration and human capital formation, we show - somewhat against the conventional wisdom - that low-skill immigration may lead to a lower tax burden and less redistribution than would be the case with no immigration, even though migrants (naturally) join the pro-tax/transfer coalition. Data on 11 European countries over the period 1974 to 1992 are consistent with the implications of the theory: a higher share of immigrants in the population leads to a lower tax rate on labor income, with the effect statistically significant even after controlling for the generosity and size of the welfare state, demographics, and the international exposure of the economy. As predicted by the theory, it is the increased share of low-education immigrants that leads to the smaller tax burden.
Keywords: D3; D7; F22; J61; 330; migration; political-economy equilibrium; tax-transfer policy